European Treatment and Outcome Study score does not predict imatinib treatment response and outcome in chronic myeloid leukemia patients. Issue 1 (23rd January 2014) - Yamamoto, Eri; Fujisawa, Shin; Hagihara, Maki; Tanaka, Masatsugu; Fujimaki, Katsumichi; Kishimoto, Kumiko; Hashimoto, Chizuko; Itabashi, Megumi; Ishibashi, Daisuke; Nakajima, Yuki; Tachibana, Takayoshi; Kawasaki, Rika; et al.
<x xml:space="preserve">Abstract</x> The Sokal and Hasford scores were developed in the chemotherapy and interferon era and are widely used as prognostic indicators in patients with chronic myeloid leukemia (CML). Recently, a new European Treatment and Outcome Study (EUTOS) scoring system was developed. We performed a multicenter retrospective study to validate the effectiveness of each of the three scoring systems. The study cohort included 145 patients diagnosed with CML in chronic phase who were treated with imatinib. In the EUTOS low‐ and high‐risk groups, the cumulative incidence of complete cytogenetic response (CCyR) at 18 months was 86.9% and 87.5% (P = 0.797) and the 5‐year overall survival rate was 92.6% and 93.3% (P = 0.871), respectively. The cumulative incidence of CCyR at 12 months, 5‐year event‐free survival and 5‐year progression‐free survival were not predicted using the EUTOS scoring system. However, there were significant differences in both the Sokal score and Hasford score risk groups. In our retrospective validation study, the EUTOS score did not predict the prognosis of patients with CML in chronic phase treated with imatinib.